Caustic Mist Exposure and Respiratory Outcomes in a Cohort Study of Alumina Refinery Workers. Issue 6 (18th March 2021) - Benke, Geza; Del Monaco, Anthony; Dennekamp, Martine; Dimitriadis, Christina; Gwini, Stella M; de Klerk, Nicholas; Musk, Arthur William; Fritschi, Lin; Abramson, Michael J; Sim, Malcolm R
Abstract: A common chemical exposure in alumina refining is caustic mist. Although recognized as a strong airways irritant, little is known of the chronic respiratory effects of caustic mist in alumina refining. A suitable metric for caustic mist exposure assessment in alumina refining for epidemiological purposes has not been identified. Peak exposure is likely to be important, but is difficult to assess in epidemiological studies. In this study, we investigate the respiratory effects of caustic mist in an inception cohort ( n = 416) of alumina refinery workers and describe the development and use of a peak exposure metric for caustic mist. We then compare the results with a metric based on duration of exposure. Participants were interviewed annually about respiratory symptoms and had a lung function test. Job history data were collected from each interview and levels of caustic mist were measured periodically by air monitoring. We found a weak association between the caustic mist peak exposure metric and reported cough ( P for linear trend = 0.079) with the highest peak exposure group odds ratio = 2.32 (95% confidence interval: 1.27, 4.22). For lung function, we found declines in the forced expiratory volume in 1 second and forced vital capacity for changes in annual and absolute lung function for both metrics of exposure, but only the ratio of absolute lung function was statistically associated with an increasing duration of caustic exposure ( P for linear trend = 0.011). In this cohort, we did not observe an association with respiratory symptoms or consistent decrements in lung function. There was little difference between the exposure metrics used for investigation of the chronic effects from caustic mist.